When do forecasts fail and when not? Contingencies affecting the accuracy of sales managers' forecast regarding the future business situation. Issue 3 (3rd July 2021) - Schneider, Janina-Vanessa; Alavi, Sascha; Guba, Jan Helge; Wieseke, Jan; Schmitz, Christian
Abstract: Improving business forecasts is a major goal of many companies because of its strong positive impact on future performance and potential competitive advantages. Even though sales managers have been called to serve as a profound base for business forecasts from a theoretical perspective, this premise has not been subject to empirical testing to date. Addressing this research void, the authors analyze under which conditions sales managers' business forecasts are reliable and when not. The authors conducted a cross-industry field study including two measurement points with 180 high-ranking senior sales managers. Results show that managers' forecast accuracy fundamentally depends on contextual moderators. Sales managers predict future business situations 2.5 times more accurate when they exhibit a long firm-specific experience and high confidence-levels in their own forecast. Furthermore, a comparably long sales cycle improves forecast accuracy. Conversely, sales managers may make considerable misjudgments if the before mentioned conditions are not met.